The use of the cavitation effect in the mitigation of CaCO sub 3 deposits - Heath, David John (Strojniški vestnik, 2013)
Hard mineral scale fouling results in significant economic losses both industrially and domestically. Recently, attempts have been made to use ultrasound to mitigate scale formation and its removal based on the phenomena of cavitation. Cavitation erosion is the removal of material from a solid surface by pressure shock waves associated with the formation and collapse of bubbles. This paper reviews the literature on cavitation erosion of brittle crystalline materials in an attempt to better understand the relationship between the material properties of CaCO3 scale deposits and its potential removal by cavitation. The study finds that from a materials perspective cavitation erosion is intimately associated to both a materials bulk properties and importantly to its microstructure. The situation is further complicated because the macro and micro-properties of CaCO3 scale are dependent on many factors relating to its depositional environment. The type of scale formed will affect how it is removed by cavitation.
Keywords: calcium carbonate; cavitation; erosion; kalcijev karbonat; kavitacija; kavitacijska erozija; prenosnik toplote; scale; ultrasound; ultrazvok; vodni kamen